Breeding soundness of stud bulls - Shaha, SP; Alam, MGS; Khatun, M; Ahmed, JU (Bangladesh Veterinarian, 2010)
Four bulls of mixed breeds (Sahiwal × Zebu, Sindhi × Zebu, Jersey × Zebu and Holstein-Friesian × Zebu )were examined physically and their semen was evaluated in three seasons: I (Rainy): May - November, II (Winter): December - February, III (Summer): March- April. The semen volume, sperm motility, sperm concentration and percentage of dead sperm ranged from 4.1 to 7.6 ml, 56.6 to 76%, 1010.3 to 1290.7 × 106/ml and 18.4 to 24.7%, respectively. All these attributes varied significantly (p<0.05) between breeds and seasons. The variations of semen quality between breeds were not significant (p>0.05). It is suggested that the Holstein - Friesian × Zebu crossbred bull produces better quality semen than others. DOI: 10.3329/bvet.v25i2.4618 Bangl. vet. 2008. Vol. 25, No. 2, 51-61